Comparative Evaluation of Single‐Well LNAPL Tracer Testing at Five Sites. Issue 2 (6th June 2016) - Pennington, Andrew; Smith, Jonathon; Koons, Brad; Divine, Craig E.
Abstract: Light nonaqueous phase liquid (LNAPL) tracer testing is a technique used to directly measure LNAPL flow in situ and evaluate LNAPL mobility and recoverability. The test method consists of adding a fluorescent oil‐soluble tracer to LNAPL within a well, isolating small volumes of LNAPL with known tracer concentrations for use as in‐well calibration standards, and measuring the rate of tracer concentration decline in the well over time. The test measures LNAPL flux through the well, which is directly related to LNAPL mobility and recoverability in the surrounding formation. Test results for a total of 29 wells at five sites are presented. Results from LNAPL tracer testing were comparable to results obtained through other methods, and the method offers a time‐averaged result measured over a relatively long period, in ambient conditions, and reflects the influences of heterogeneity and hydraulic changes. In some cases, tracer concentration decline followed unexpected patterns, and these data have led to a better understanding of test assumptions, mechanisms influencing tracer distribution, and options to improve test execution and data interpretation. Method improvements developed over the course of the field studies included refinement of pre‐test screening of LNAPL fluorescence and improvements to measurement equipment. Overall, the field studies confirmed the technical validity and usefulness of the LNAPL tracing technique to support LNAPL mobility and recoverability assessments.